Bistachybotrysin K, one new phenylspirodrimane dimer from Stachybotrys chartarum with potent cytotoxic activity. Issue 5 (3rd May 2020) - Jia, Xiao-Na; Zhao, Jin-Lian; Feng, Jia-Min; Chen, Ri-Dao; Xie, Ke-Bo; Chen, Da-Wei; Li, Yan; Liu, Ji-Mei; Dai, Jun-Gui
Abstract: Bistachybotrysin K (1 ), one new phenylspirodrimane dimer with a central 6/7 oxygen heterocycle core, was isolated from the fungus Stachybotrys chartarum CGMCC 3.5365. Its structure was elucidated by extensive spectroscopic data and single-crystal X-ray diffraction. Compound 1 showed significant cytotoxicity against human tumor cell lines HCT116, NCI-H460, BGC823, Daoy, and HepG2 with IC50 values in the range of 1.1–4.7 µM. Graphical Abstract: